'Sedimented histories' and 'embodied legacies': Creating an evaluative framework for understanding public engagement with the First World War. (1st February 2020) - Allwork, Larissa
Abstract : This article reflects on the development of a new methodological framework for the evaluation of the impact of the Centre for Hidden Histories, one of the Arts and Humanities Research Council's First World War Engagement Centres. It shows how through evaluative processes such as academic and community partner Shared Experience Workshops, and community-focused Reflection Workshops, the historical, social, cultural and economic benefits of the centre can be highlighted. It also demonstrates how public engagement in these community history projects has resulted in the identification of new 'embodied legacies' (Facer and Enright, 2016) and heretofore marginalized 'sedimented histories' (Lloyd and Moore, 2015). These lessons in evaluation can be taken forward to inform future national commemorative moments, such as the centenary of the Second World War.